1994
DOI: 10.1039/an9941902651
|View full text |Cite
|
Sign up to set email alerts
|

Stability of zeranol, nandrolone and trenbolone in bovine urine

Abstract: The stability of some growth promoting agents in cattle urine, under various temperature storing conditions, was investigated. Bovine urine samples obtained from previous excretion studies which contained zeranol, nandrolone and trenbolone respectively, were stored frozen, at room temperature and in direct sunlight. On days 0, 2, 4, 7 and 10, zeranol and nandrolone were quantified by selective ion monitoring analysis on a gas chromatography-mass selective detector and trenbolone by using an enzyme linked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Nandrolone is administered as an anabolic agent for fattening veal calves and cattle, although the use of hormones for growth-promotion or fattening is prohibited in the EU [21, 22]. The retention time of the purchased nandrolone corresponded to one low-intensity peak within an isomer cluster of the accurate mass.…”
Section: Resultsmentioning
confidence: 99%
“…Nandrolone is administered as an anabolic agent for fattening veal calves and cattle, although the use of hormones for growth-promotion or fattening is prohibited in the EU [21, 22]. The retention time of the purchased nandrolone corresponded to one low-intensity peak within an isomer cluster of the accurate mass.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the stability of TbOH in bovine urine showed that storage of urine samples in direct sunlight led to decreased TbOH concentrations (25). Storage of feces samples at room temperature in some cases caused partial or complete loss of the TbOH-17α content (26).…”
Section: Studies I and Iimentioning
confidence: 99%
“…Some types of degradation of steroids by bacteria have already been demonstrated in studies carried out on human urine,1, 4 but few data are available on equine or bovine urine 5. Microbiological activity seems to depend on urine storage temperature, highlighting the necessity to maintain the cold chain in order to preserve urine samples unaltered, from the moment of collection to that of antidoping analysis 2.…”
mentioning
confidence: 99%